The sacrificed body : Balkan community building and the fear of freedom - Aleksić, Tatjana (Series in Russian and East European studies., 2013)
"Tatjana Aleksic examines the widespread use of the sacrificial metaphor in cultural texts and its importance to sustaining communal ideologies in the Balkan region. Aleksic further relates the theme to the sanctioning of ethnic cleansing, rape, and murder in the name of homogeneity and collective identity. She employs cultural theory, sociological analysis, and human rights studies to expose a historical narrative that is predominant regionally, if not globally"--